Intraocular Microsurgical Forceps (20, 23, and 25 gauge) Membrane Peeling Forces Assessment - Raul Velez-Montoya; Chirag Patel; Scott C. N. Oliver; Hugo Quiroz-Mercado; Naresh Mandava; Jeffrey L. Olson (Journal of Ophthalmology)
Background. To assess the peeling forces exerted by different calibers of microsurgical forceps on an experimental model of epiretinal membrane. Methods. A model of epiretinal membrane was constructed using thin cellulose paper and heptanes-isopropyl alcohol 1% mixture. The model was mounted on a force censoring device. Subsequently, flaps were created with three different microsurgical forceps of different calibers. We recorded the number of attempts, the duration of the event, and the pushing and the pulling forces during the peeling. The results were compared by a one-way ANOVA and a Fisher unprotected least significant difference test with an alpha value of 0.05 for statistically significance. Results. There was a statistical significant difference on the pulling and pushing forces between the 25 gauge (13.79 mN; −13.27 mN) and the 23 (6.63 mN; −5.76 mN) and 20 (5.02 mN; −5.30 mN) gauge, being greater in the first (). There were no differences in the duration of all events, meaning that all the forces were measured within the same period of time. Conclusions. The 25 gauge microsurgical forceps exerted the greatest mechanical stress over our simulated epiretinal membrane model and required more attempts to create a surgical suitable flap. The clinical implication of this finding is still to be determined.